Non-suicidal Self-Injury in Eating Disordered Patients: Associations with Heart Rate Variability and State-Trait Anxiety - Giner-Bartolome, Cristina; Mallorquí-Bagué, Núria; Tolosa-Sola, Iris; Steward, Trevor; Jimenez-Murcia, Susana; Granero, Roser; Fernandez-Aranda, Fernando (Frontiers in Psychology, 2017)
Background: Non-suicidal self-injury (NSSI) is commonly present in individuals with eating disorders (ED) and is often employed as a maladaptive emotion regulation strategy to avoid or abate negative emotions. One of the most prevalent negative emotions experienced by self-injurers is anxiety; however, this emotion has not been extensively studied in this population. Thus, the aim of our study was to investigate the influence of anxiety on NSSI in patients with ED from two different dimensions: state anxiety and trait anxiety. Methods: The study comprised a total of 66 females: 12 ED patients with NSSI, 32 ED patients without a history of NSSI, and 22 healthy controls. State and trait anxiety were assessed by means of State-Trait Anxiety Inventory (STAI-S-T) and physiological data [i.e. heart rate variability (HRV)] were collected. Results: STAI-trait scores were significantly higher in ED patients with NSSI than ED patients without NSSI. Furthermore, when conducting logistic regression analyses higher STAI-trait scores were associated with NSSI in ED patients. However, no differences in STAI-state scores and HRV were found between ED patients with and without NSSI. Discussion: The present findings suggest that anxiety as a trait is associated with the use of maladaptive strategies (i.e. NSSI) in ED patients. These results uphold the need to target trait anxiety in ED treatment in order to prevent possible NSSI behaviors.